Local Councils and Education (Journal of Parents and Teachers, 2026)
As this article reports, it is a fact that, for various reasons, local councils are having an increasingly significant and systematic impact on the education sector. The article highlights the experiences of a number of local councils where their influence on education is clearly evident through initiatives, programmes and activities, which are detailed in the article.
Keywords: Local Councils and Education